Turning Waste into Wealth: Empowering Rural Communities through TPS3R and Circular Economy Innovation in Collaboration with Kopernik in Bali - Panasea, I Gede Nandya Oktora; Dewi, Luh Gede Krisna; Suasih, Ni Nyoman Reni; Yasa, I Made Putra; Narindra, Nyoman Diestha Putra; Pradnyani, Ida Ayu Dipavali (PT Inovasi Pratama Internasional, 2025)
The issue of household organic waste in rural areas remains a significant environmental and socioeconomic challenge, particularly in Gulingan Village, Mengwi District, Badung Regency. The high volume of organic waste, low awareness of waste separation, and the untapped economic potential of processed waste form the background of this initiative. This community service program was carried out in collaboration with the NGO Kopernik as a strategic partner through technical training, environmental education, and institutional strengthening based on the circular economy. The implementation methods included public outreach, participatory mapping, training in making compost and eco-enzymes, household mentoring, as well as pre-test and post-test evaluations to assess participants’ improved understanding. The results showed a significant increase in participants’ awareness and skills. Based on the evaluation, understanding of waste separation rose from 52% to 82%, while active participation in processing practices increased from 44% to 72%. This activity demonstrates that practice-based and collaborative approaches can strengthen community capacity in realizing a sustainable and environmentally resilient village.